2013
DOI: 10.1111/tpj.12109
|View full text |Cite
|
Sign up to set email alerts
|

An ATP synthase harboring an atypical γ–subunit is involved in ATP synthesis in tomato fruit chromoplasts

Abstract: SUMMARYChromoplasts are non-photosynthetic plastids specialized in the synthesis and accumulation of carotenoids. During fruit ripening, chloroplasts differentiate into photosynthetically inactive chromoplasts in a process characterized by the degradation of the thylakoid membranes, and by the active synthesis and accumulation of carotenoids. This transition renders chromoplasts unable to photochemically synthesize ATP, and therefore these organelles need to obtain the ATP required for anabolic processes throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Nievelstein et al (1995) observed a similar respiratory response to NADH, NADPH, and the uncoupler 2,4-dinitrophenol in chromoplasts isolated from daffodil flowers. Pateraki et al, (2013) recently reported the stimulatory effect of NADPH and CCCP on oxygen uptake rates in tomato chromoplasts. Our results are also consistent with the reported existence of an active H + -ATP synthase in tomato (Pateraki et al, 2013) and daffodil (Morstadt et al, 2002) chromoplasts.…”
Section: Chromoplast Respiratory Activity Is Linked To Atp Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Nievelstein et al (1995) observed a similar respiratory response to NADH, NADPH, and the uncoupler 2,4-dinitrophenol in chromoplasts isolated from daffodil flowers. Pateraki et al, (2013) recently reported the stimulatory effect of NADPH and CCCP on oxygen uptake rates in tomato chromoplasts. Our results are also consistent with the reported existence of an active H + -ATP synthase in tomato (Pateraki et al, 2013) and daffodil (Morstadt et al, 2002) chromoplasts.…”
Section: Chromoplast Respiratory Activity Is Linked To Atp Synthesismentioning
confidence: 99%
“…Pateraki et al, (2013) recently reported the stimulatory effect of NADPH and CCCP on oxygen uptake rates in tomato chromoplasts. Our results are also consistent with the reported existence of an active H + -ATP synthase in tomato (Pateraki et al, 2013) and daffodil (Morstadt et al, 2002) chromoplasts.…”
Section: Chromoplast Respiratory Activity Is Linked To Atp Synthesismentioning
confidence: 99%
See 3 more Smart Citations